Adrenocortical hypofunction with simultaneous primary aldosteronism: A case report. Issue 13 (March 2019) - Liang, Kaiyong; Ou, Xiaojuan; Huang, Xukai; Lan, Qunfang
Abstract: Rationale: Cases of adrenocortical hyperfunction combined with primary aldosteronism have been reported in the literature, and the underlying mechanism involves the secretion of aldosterone and glucocorticoids by a tumor or an adenoma. However, adrenocortical hypofunction and coexisting primary aldosteronism have not been reported until now. Herein, we report a case of adrenocortical hypofunction combined with primary aldosteronism. Patient concerns: A 66-year-old Chinese woman with rheumatoid arthritis who had been diagnosed with secondary adrenal insufficiency and was taking prednisone acetate tablets for replacement treatment presented to our department. She also had type 2 diabetes mellitus, osteoporosis, bilateral knee osteoarthritis, and lumbar vertebral compression fracture. She had previously developed tuberculosis, which had been cured. Diagnosis: The cortisol and adrenocorticotropic hormone rhythm indicated cortisol dysfunction in the patient. A 64-slice computed tomography and magnetic resonance imaging both showed bilateral adrenal hyperplasia. A postural stimulation test indicated a high level of aldosteronism and a high aldosterone-to-renin ratio (ARR, supine position: aldosterone 1788.73 pg/mL, ARR 146.62; upright position: aldosterone 2916.21 pg/mL, ARR 92.29). The captopril test showed the aldosterone level decreased by 364.70 pg/mL 1 hour after administration of captopril (from 2153.28 to 1788.58 pg/mL). The decline in aldosterone level was approximately 16.90% (i.e., <30%), and the ARR was still >40. Based on the above-mentioned findings, we diagnosed the patient with adrenocortical hypofunction with primary aldosteronism. Interventions: We administered spironolactone 20 mg twice daily and continued the glucocorticoid replacement therapy. Outcomes: One week after diagnosis, the patient had an aldosterone level of 2201.16 pg/mL, plasma renin activity of 3.88 ng/mL/h, and an ARR of 56.7 (upright position). Her blood pressure was maintained within the normal range. Lessons: Although adrenocortical hypofunction with primary aldosteronism is rare, cases of primary aldosteronism complicated with hypercortisolism are occasionally encountered. Hence, whenever possible, we recommend testing both aldosterone and cortisol levels in all patients with adrenal dysfunction.